An Exploratory Trial of Two Dosages of a Novel Synthetic Thrombin Inhibitor (Napsagatran, Ro 46-6240) Compared with Unfractionated Heparin for Treatment of Proximal Deep-vein Thrombosis - Bounameaux, Henri; Ehringer, Herbert; Hulting, Johan; Rasche, Herbert; Rapold, Hans J; Zultak, Maurice; ADVENT Investigators (Thrombosis and Haemostasis, 1997)
One hundred and ten patients with acute proximal deep-vein thrombosis were randomized in a sequential dose-finding design, to receive continuous intravenous infusion of napsagatran, a novel synthetic thrombin-inhibitor, at a fixed dose of 5 mg/h (n = 37) or 9 mg/h (n = 26), or APTT-adjusted unfractionated heparin (n = 47). Oral anticoagulants were started on the 2nd day and the study drug was discontinued from the 5th treatment day, as soon as the International Normalized Ratio was above 2.Control venogram (97 venogram pairs evaluable) after 5-8 days of treatment showed improvement in 3 napsagatran-treated patients (versus none in heparin-treated patients) and worsening in 4 napsagatran- treated patients (versus 2 in heparin-treated patients). The venographic Marder’s score did not change among the treatment groups. New lung scan perfusion defects (99 scintigram pairs evaluable) occurred in 4 (11%), 4 (21%), and 4 (10%) patients in the napsagatran (5 mg/h) group, in the napsagatran (9 mg/h) group, and in the heparin control group, respectively. There was no statistically significant difference in any of these endpoints between the 3 groups. No major bleeding was observed and the rare minor bleedings occurred at a similar rate in the three treatment groups.In conclusion, the ADVENT trial has shown data that suggest comparable efficacy and safety of a synthetic, direct thrombin inhibitor (napsagatran) and conventional heparin therapy for treatment of proximal DVT. These results suggest that synthetic direct thrombin inhibitors are a promising class of antithrombotic agents which deserves further development in this field.